Light transmittance of CAD/CAM ceramics with different shades and thicknesses and microhardness of the underlying light-cured resin cement - Zahra Jafari; Homayoon Alaghehmand; Yasaman Samani; Mina Mahdian; Soraya Khafri (Restorative Dentistry & Endodontics, 2018)
ObjectivesThe aim of this in vitro study was to evaluate the effects of the thickness and shade of 3 types of computer-aided design/computer-aided manufacturing (CAD/CAM) materials.Materials and MethodsA total of 120 specimens of 2 shades (A1 and A3) and 2 thicknesses (1 and 2 mm) were fabricated using VITA Mark II (VM; VITA Zahnfabrik), IPS e.max CAD (IE; IvoclarVivadent), and VITA Suprinity (VS; VITA Zahnfabrik) (n = 10 per subgroup). The amount of light transmission through the ceramic specimens was measured by a radiometer (Optilux, Kerr). Light-cured resin cement samples (Choice 2, Bisco) were fabricated in a Teflon mold and activated through the various ceramics with different shades and thicknesses using an LED unit (Bluephase, IvoclarVivadent). In the control group, the resin cement sample was directly light-cured without any ceramic. Vickers microhardness indentations were made on the resin surfaces (KoopaPazhoohesh) after 24 hours of dark storage in a 37°C incubator. Data were analyzed using analysis of variance followed by the Tukey post hoc test (α = 0.05).ResultsCeramic thickness and shade had significant effects on light transmission and the microhardness of all specimens (p < 0.05). The mean values of light transmittance and microhardness of the resin cement in the VM group were significantly higher than those observed in the IE and VS groups. The lowest microhardness was observed in the VS group, due to the lowest level of light transmission (p < 0.05).ConclusionGreater thickness and darker shades of the 3 types of CAD/CAM ceramics significantly decreased the microhardness of the underlying resin cement.